Helminth species richness in wild wood mice, Apodemus sylvaticus, is enhanced by the presence of the intestinal nematode Heligmosomoides polygyrus - Behnke, J.M.; Eira, C.; Rogan, M.; Gilbert, F.S.; Torres, J.; Miquel, J.; Lewis, J.W. (Cambridge University Press, 2009)
We analysed 3 independently collected datasets of fully censused helminth burdens in wood mice, Apodemus sylvaticus, testing the a priori hypothesis of Behnke et al. (2005) that the presence of the intestinal nematode Heligmosomoides polygyrus predisposes wood mice to carrying other species of helminths. In Portugal, mice carrying H. polygyrus showed a higher prevalence of other helminths but the magnitude of the effect was seasonal. In Egham, mice with H. polygyrus showed a higher prevalence of other helminth species, not confounded by other factors. In Malham Tarn, mice carrying H. polygyrus were more likely to be infected with other species, but only among older mice. Allowing for other factors, heavy residual H. polygyrus infections carried more species of other helminths in both the Portugal and Egham data; species richness in Malham was too low to conduct a similar analysis, but as H. polygyrus worm burdens increased, so the prevalence of other helminths also increased. Our results support those of Behnke et al. (2005), providing firm evidence that at the level of species richness a highly predictable element of co-infections in wood mice has now been defined: infection with H. polygyrus has detectable consequences for the susceptibility of wood mice to other intestinal helminth species.